The Ugaritic Baal cycle. - Smith, Mark S. (Vetus Testamentum, Supplements, 1994)
The Ugaritic Baal Cycle offers a translation and the first commentary on the Ugaritic Baal Cycle. The longest and most important religious text from ancient Ugarit, the Baal Cycle witnesses to both the religious worldview of Ugarit and the larger background to many of the formative religious concepts and images in the Bible. The volume treats introductory matters such as date, order and continuity of the tablets, the history of interpretation, and finally a new proposal for the interpretation of text drawing on the insights of previous views as well as newer evidence. The commentary proper provides bibliography, text, textual notes, literary structure and detailed commentary for each column in the first two tablets.